1981
DOI: 10.1177/000348948109000208
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Blood-Labyrinth Barrier in Experimental Conditions

Abstract: The blood-labyrinth barrier is concept that has evolved based on marked difference in chemical composition between perilymph and blood. Studies reported here have been designed to manipulate physiologic, metabolic, and pharmacologic conditions in experimental animals in order to determine the characteristics of this regulatory mechanisms. Tracer studies of uptake of sodium, calcium, and albumin from blood into perilymph showed that these substances penetrate into inner ear fluids quite slowly. Injections of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
3

Year Published

1982
1982
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 21 publications
0
51
0
3
Order By: Relevance
“…However, the 10-14μm-thick round window membrane in the chinchilla has been observed to pass macromolecules as large as 70kDa (Goycoolea and Lundman, 1997;Goycoolea et al, 1988). While (-)-pentazocine's relatively high tissue solubility (Walker et al, 1990) and relatively low molecular weight additionally argue for an easy passage across the blood-labyrinthine barrier (Juhn et al, 1981), additional studies are required to determine the precise amount of recoverable perilymphatic (-)-pentazocine following i.v. administrations in this species.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 10-14μm-thick round window membrane in the chinchilla has been observed to pass macromolecules as large as 70kDa (Goycoolea and Lundman, 1997;Goycoolea et al, 1988). While (-)-pentazocine's relatively high tissue solubility (Walker et al, 1990) and relatively low molecular weight additionally argue for an easy passage across the blood-labyrinthine barrier (Juhn et al, 1981), additional studies are required to determine the precise amount of recoverable perilymphatic (-)-pentazocine following i.v. administrations in this species.…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the barrier is critical for maintaining inner ear homeostasis, especially for sustaining the endocochlear potential (EP), an essential driving force for hearing function (1)(2)(3)(4). Disruption of the barrier is closely associated with a number of hearing disorders, including autoimmune inner ear disease, noise-induced hearing loss, agerelated hearing loss, and several genetically linked diseases (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…In the classic view, the intrastrial fluid-blood barrier comprises basement membrane and endothelial cells (ECs) that connect to each other with tight junctions (11) to form a diffusion barrier that prevents most blood-borne substances from entering the ear (2). In a recent study, we found that the intrastrial fluid-blood barrier also includes a large number of pericytes and perivascular-resident macrophage-like melanocytes (PVM/Ms) (12,13).…”
mentioning
confidence: 99%
“…The uptake of systemically administered compounds into the central nervous system is very low due to the protective blood-brain barrier which prevents entry of many useful medications (Persidsky et al, 2006). Similarly, the blood-labyrinth barrier prevents compounds in the blood supply from entering the inner ear (Inamura and Salt, 1992;Juhn, 1988;Juhn et al, 1981Juhn et al, , 2001. The development of minimally invasive methods for localized and sustained delivery of precise quantities of medication near the implant site will circumvent these barriers and enable improvements in the safety, efficacy, cost, and reliability of APs while reducing adverse effects.…”
Section: Pharmaceuticals For Improved Auditory Prosthesis Therapymentioning
confidence: 99%